Pengaruh Promosi, Selebgram Endorsment Dan Brand Ambassador Terhadap Minat Pembelian Produk Madame Gie Kosmetik (Studi Kasus Konsumen di Kelurahan Merjosari Kota Malang) - Nadifah, Siti Rogibatun; Arifin, Rois; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze and describe the influence of promotions, celebrity endorsements and brand ambassadors on purchasing interest in Madam Gie cosmetic products (case study of consumers in Merjosari Village, Malang). The population in this study were consumers of Madam Gie products in Merjosari Village in Malang City. A sample of 80 people was obtained using the Malhotra formula. The variables used in this research are the purchase interest variable (dependent variable), while the independent variables are promotion, celebrity endorsement and brand ambassador. The results of this research conclude that the influence variables of promotion, celebrity endorsement and brand ambassador simultaneously influence purchase interest. and partially concluded that there is a variable influence of promotion, celebrity endorsement and brand ambassador on purchasing interest. Keywords: Purchase Interest, Promotion, Celebrity Endorsement And Brand Ambassador.